Building National Character: The Role of Character Education in History Learning - Nurzafimala, Nurzafimala; Namatsi, Beatrice A; Hong, Sung Ku (Indonesian Journal of Education Research (IJoER), 2024)
Purpose of the study: The purpose of this study is to determine the general description of Senior High School Number 1 Gunung Talang and the implementation of character education in history learning at Senior High School Number 1 Gunung Talang. Methodology: This research is qualitative-descriptive. To conduct the research, data sources are needed, both primary and secondary sources. Data collection used is observation, interviews and documentation. Data analysis techniques include collecting data, data reduction, data presentation and drawing conclusions. Triangulation data validity techniques. Main Findings: Senior High School Number 1 Gunung Talang was established to address the lack of high schools in Solok Regency, especially for students from Cupak and nearby areas. Character education is integrated into the lesson plans and history learning process through group discussions, respect for others' opinions, religious habits, and discipline. It is evaluated based on students' attitudes during learning. Supporting factors include ample time and adequate facilities, but challenges arise as teachers cannot monitor students' behavior outside the classroom, where environmental influences play a role. Novelty/Originality of this study: This study shows that history learning can be an effective means of forming national character through the instillation of moral values. With the integration of educational character, students not only learn historical events, but also develop attitudes of discipline, mutual respect, and religious values ​​that support the formation of national character.